Effect of Evaporative Cooling by Misting Fan on Microclimate of a Naturally Ventilated Greenhouse - Sulaiman, Ahmad Syafik Suraidi (2008)

(untitled)
The environment that suits the growth of most kind of crops is very crucial in order to guarantee high quality yields that can be controlled according to the desired parameters and not easily damaged or stunted during its growth. Naturally Ventilated Greenhouse (NVGH) is one of the methods to attain the controlled environment and it is proven to be highly effective in controlling the suitable environment for most kind of plants or vegetables. Furthermore, NVGH can save energy where mechanical, electrical and labour power required is very small, require no controlling procedures or complicated handling, suitable to tropical climate and the cost to build is very low compared to other plant protection structures. The tropical country climate is inconsistent all year long and even though the NVGH can control its environment, it has some weaknesses in which the air and the temperature inside the NVGH can be easily influenced by the outside conditions of the structure. Most kinds of crops require temperature between 20-35ºC and relative air humidity between 80-90% in order to ensure a standard quality harvest. An evaporative cooling system using four misting fans was studied inside a NVGH of 10m width, 50m long and 4m high. The aim was to modify the environment inside the NVGH so that it could control the inside temperature between 20-35ºC and relative humidity between 80-90% all day long. Other environmental parameters such as light intensity, outside air temperature and carbon dioxide were also studied in order to see the correlation and modification effect on the environment in the NVGH. All environment data studied was recorded and statistically analyzed using the Statistical Package for the Social Science (SPSS) software. Temperature inside the NVGH was found to be strongly correlated with time (min), outside temperature, light intensity and relative air humidity while carbon dioxide only gave a moderate effect on the temperature inside the NVGH. The correlation equation between temperature inside the NVGH is shown in the following equation: T1= -0.001 (T) +0.001 (L)-0.103 (H) +0.447 (T2) +21.949 where T1= inside temperature (°C), T= Time (min) L= Light Intensity (W·m-2), H=Relative Humidity (%) and T2= outside temperature (°C). The misting fans also turned out to be effective in controlling the temperature inside the NVGH to remain between 20-35ºC and relative air humidity between 80-90% all day long compared to NVGH that is not equipped with the misting fans. The inside temperature, light intensity and carbon dioxide under the NVGH attached with misting fans were found to be lower than NVGH without misting fans. The relative humidity inside the NVGH attached with misting fans was found to be higher than the NVGH without misting fans. Crop such as chili and cauliflowers were able to grow favourably inside the NVGH attached with the misting fans and the crop growth performance indicates a linear trend during the growing period.